Scour Protection Around Bridge Pier Using Based Ramp - Thunyaphun, Tussanun; Kositgittiwong, Duangrudee; Ekkawatpanit, Chaiwat; Sukjan, Rachapol (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 25, 2020)
The purposes of this study will innovate the scour protection system around bridge piers reducing the depth and size of scour by using based ramp protection. Bridge piers are substructure which strongly used to support bridges. It appears that one of the main causes of bridge pier failure is scour. Scour is a hydrodynamic process that remove the sediment around bridge piers caused by flow separation as well as vortexes developing also known as scour hole. For the reason, bridge piers able to fail in case there is not enough protection and attentive consideration. The experiments were carried out in the large-sized open-channel flume at KMUTT. The scour mechanism and the time-varied development of scour depth were studied. The based ramps for scour protection were designed and differentiated into four different size and shape in order to find the most effective protection and reduction for scour. Maximum depth and 12-measuring points around the curb of the scour hole were measured and collected. In the first 60 minutes, the measuring point reading was recorded every 10 minutes, and then every 30 minutes until reaching 120 minutes. The test results show the maximum scouring depth is increasing in the function of time. An unprotection pier without based ramp was conducted to be the reference. The cases with based ramp protection then carried out to compare and analyze the protection efficiency.